2006
DOI: 10.1002/rcm.2566
|View full text |Cite
|
Sign up to set email alerts
|

New surfaces for desorption electrospray ionization mass spectrometry: porous silicon and ultra‐thin layer chromatography plates

Abstract: The performance of nanoporous silicon (pSi) and ultra-thin layer chromatography (UTLC) plates as surfaces for desorption electrospray ionization (DESI) was compared with that of polymethyl methacrylate (PMMA) and polytetrafluoroethylene (PTFE), both popular surfaces in previous DESI studies. The limits of detection (LODs) and other analytical characteristics for six different test compounds were determined using all four surfaces. The LODs for the compounds were in the fmol-pmol (pg-ng) range. The LODs with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 20 publications
3
75
0
Order By: Relevance
“…Surface variables including the chemical composition, porosity, texture, and electrical conductivity of the substrate have been reported to affect DESI analyses [2,24,[37][38][39]. Dramatic reductions in response have been noted for high conductivity surfaces due to neutralization of the incoming ion plume at the surface [2,38].…”
Section: Esorption Electrospray Ionization (Desi)mentioning
confidence: 99%
See 3 more Smart Citations
“…Surface variables including the chemical composition, porosity, texture, and electrical conductivity of the substrate have been reported to affect DESI analyses [2,24,[37][38][39]. Dramatic reductions in response have been noted for high conductivity surfaces due to neutralization of the incoming ion plume at the surface [2,38].…”
Section: Esorption Electrospray Ionization (Desi)mentioning
confidence: 99%
“…If a more volatile solvent is used (e.g., methanol), the evaporation time may be reduced; however the low surface tension of the solvent makes uniform sample deposition more challenging [2]. Furthermore, sample analyses that utilize smooth surfaces are typically prone to erosion effects, thereby requiring alternative deposition onto porous or rough surfaces that retain the adsorbed analyte during the formation of the initial solvation layer [2,37,39]. The mesh materials used for TM-DESI overcome these difficulties by suspending both high and low volatility deposition solvents of varying surface tensions in the open space of a mesh.…”
Section: Desorption Of Liquid Samples From Mesh Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been shown that several experimental parameters can be optimized to improve the quality of DESI data. [9,15] Two distinctive mass spectral patterns were observed in the negative-ion mode for the brain sections analyzed depending on the region of the brain being investigated (Figure 1). The differences are associated with the lipid compositions representative of the gray and white matter of the brain.…”
mentioning
confidence: 99%